2011
DOI: 10.1002/crat.201000676
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution semi‐automatic crystallite orientation and phase mapping of nanocrystals in transmission electron microscopes

Abstract: International audienceA semi-automatic technique for the mapping of nanocrystal phases and orientations in a transmission electron microscope (TEM) is described. It is based primarily on the projected reciprocal lattice geometry, but also utilizes the intensity of reflections that are extracted from precession-enhanced electron diffraction spot patterns of polycrystalline materials and multi-material composites. At the core of the method, experimental (precession-enhanced) electron diffraction spot patterns ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 28 publications
0
77
0
Order By: Relevance
“…26), making it almost impossible to study their local structures using electron diffraction in TEM [103]. Nevertheless, the analysis with ASTAR software of HRTEM images acquired on a Cs objective lens corrected TEM allows us to fill this gap [63,104]. Indeed post analysis with ASTAR software replacing electron diffraction pattern by Fourier transformed ones, give access to a precise evaluation of the phases contained in nanometric layers.…”
Section: Crystallographic Structure Of the Oxide Nanolayersmentioning
confidence: 99%
“…26), making it almost impossible to study their local structures using electron diffraction in TEM [103]. Nevertheless, the analysis with ASTAR software of HRTEM images acquired on a Cs objective lens corrected TEM allows us to fill this gap [63,104]. Indeed post analysis with ASTAR software replacing electron diffraction pattern by Fourier transformed ones, give access to a precise evaluation of the phases contained in nanometric layers.…”
Section: Crystallographic Structure Of the Oxide Nanolayersmentioning
confidence: 99%
“…Combining these automated indexing techniques with the nanobeam diffraction capability of the TEM, the spatial resolution of orientation mapping in the TEM can reach a 2 nm to 3 nm scale. 1 But the accuracy of measured orientations is still limited compared with the results of electron backscatter diffraction (EBSD) in the scanning electron microscope (SEM). The achievable spatial resolution of standard EBSD (s-EBSD) is still at the 20 nm-30 nm level when combined with field emission SEM, although its orientation accuracy is stable and it is generally a range of 0.5°.…”
Section: Introductionmentioning
confidence: 99%
“…A great advance would be to marry the routine quantitative capability of automated EBSD with the spatial resolution of the TEM-to be able to achieve EBSD spatial resolutions measured in the nm instead of in the tens of nm of s-EBSD. 1 In 2012, Keller and Geiss demonstrated that EBSD patterns could be acquired from a thin film specimen by transmitted electrons in the SEM. 2 They used a s-EBSD detector mounted on their SEM and a thin film specimen (TEM specimen) was tilted in the opposite direction of the standard reflection EBSD configuration to enable a geometry where a transmitted electron can hit the phosphor screen of the EBSD detector in the standard position as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Real and reciprocal space information is obtained with nanometer spatial resolution and rapid acquisition enables potentially beam sensitive materials, such as GO, to be studied. The 4D-SED dataset contains a wealth of information that can be extracted computationally post-facto [7]. In the case of GO, interpretation of the electron diffraction requires consideration of the effect of disorder, particularly on the diffracted intensities.…”
mentioning
confidence: 99%